Financial determinants of corporate reputation: A short-term approach - Blajer-Gołębiewska, Anna; Kozłowski, Arkadiusz (Managerial Economics, 2017)
The aim of this study was to verify the short-term impact of financial variables on the corporate reputation perceived by investors. In the study we applied an approach from the field of business valuation assuming that corporate reputation perceived by investors is reflected in the difference between the valuation of a company by investors and its book value. Using panel data methodology, we analysed impacts of selected financial variables, representing company’s profitability, stability and its level of risk, on these differences in valuations of selected companies listed on the Warsaw Stock Exchange. Particularly, we chose companies operating in Construction and IT sectors to represent different types of activities (industry vs. services), which impacts also the diversity in the structure of their financial statements. In the study we used multiple regression models and analysis of contingency tables (chi-squared tests of independence and Yule’s coefficient of colligation). Our data suggest that there is a lack of strong short-term relations between analysed financial variables and corporate reputation. Nevertheless, we found different determinants of corporate reputation in the Construction sector (stability and profitability as well as their changes) and in the IT sector (stability, changes in profitability and the level of financial risk).